Endograft Conformability and Aortoiliac Tortuosity in Endovascular Abdominal Aortic Aneurysm Repair. (October 2014) - Lee, Kevin; Leci, Erik; Forbes, Thomas; Dubois, Luc; DeRose, Guy; Power, Adam
Purpose: To determine conformability of stent-grafts in endovascular aneurysm repair (EVAR) using centerline of flow measurements and to compare conformability in patients with severe aortoiliac tortuosity. Methods: From 2012 to 2013, 111 consecutive patients (98 men; mean age 75.4±7.7 years) underwent endovascular aneurysm repair with Endurant I and II and Zenith Flex, LP, and Spiral Z stent-grafts; their pre- and post-EVAR computed tomography (CT) studies were retrospectively analyzed using quantitative 3-dimensional imaging software. The length between the lowest renal artery and the iliac bifurcation was measured using centerline of flow and was defined as the treatment length (TL). The difference in TLs pre and post EVAR were compared as a surrogate to evaluate endograft conformability. Results: A total of 203 pre and post EVAR aortoiliac TLs were measured (99 Endurant I, 20 Endurant II, 32 Flex, 6 LP, and 42 Spiral Z). Overall, there was a mean difference of 5.0±7.3 mm or 2.6%±3.9% between the pre- and post-EVAR TLs (p<0.001). No statistically significant difference in TLs was observed among the various stent-grafts (p=0.115). In 40 patients with severe aortoiliac tortuosity, the post-EVAR TL was 16.2±5.5 mm or 8.0%±2.7% shorter than the pre-EVAR TL (p<0.001); again, there was no difference in TLs among the various devices implanted (p=0.737). Conclusion: Overall, there was no difference in treatment lengths before and after EVAR among different stent-grafts, suggesting similar conformability. Interestingly, patients with severe aortoiliac tortuosity were found to have significantly shorter post-EVAR treatment lengths compared to before EVAR, which should be considered when planning EVAR.